Development and characterization of gluten-free bread enriched with whey protein from sorghum-rice composite flours - Borufan Itefa Achalu; Habtamu Admassu Tessema; Abebe Teshome Ayele (Applied Food Research, 2025)
The effect of baking time-temperature and incorporation of liquid whey on the physical properties of whey supplemented composite sorghum-rice gluten-free bread was investigated. Response surface methodology (RSM) using Box-Behnken design was applied to determine optimal levels of three selected processing variables such as baking temperature (160–200 °c), baking time (15–25 min) and whey proportion (20–50 %) for the production of gluten-free bread made from a rice-to-sorghum flour ratio of 80:20 %. The three level factorial design was employed to evaluate the baking quality responses (specific loaf volume, baking-loss and crumb hardness) and overall acceptability of whey supplemented gluten-free bread. Using response surface methodology, optimal values of 175 °C, 19 min, and 45 % for baking temperature, baking time, and whey proportion, respectively, were obtained. The optimal gluten‐free bread has similar baking qualities in terms of specific loaf volume; 3.16±0.068 cm3/g, baking loss; 18.21±0.069 %, hardness; 6.67±0.057 N and overall acceptability (6.34 ± 0.02 %) with commercial wheat bread which was used as a control. Results of sensory properties showed that whey incorporation in composite sorghum-rice gluten-free bread does not have an adverse impact on organoleptic characteristics and overall acceptability of the product which was better than commercial bread.